2022
DOI: 10.1038/s41598-022-13332-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer histopathology using label-free multispectral deep-UV microscopy quantifies phenotypes of tumor aggressiveness and enables multiple diagnostic virtual stains

Abstract: Identifying prostate cancer patients that are harboring aggressive forms of prostate cancer remains a significant clinical challenge. Here we develop an approach based on multispectral deep-ultraviolet (UV) microscopy that provides novel quantitative insight into the aggressiveness and grade of this disease, thus providing a new tool to help address this important challenge. We find that UV spectral signatures from endogenous molecules give rise to a phenotypical continuum that provides unique structural insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…c Blind inference of a trained virtual staining model. The virtual histology images are rapidly generated from label-free images using a digital computer smears 39 , as well as H&E 40 and IHC 41 staining on prostate tissue sections; photoacoustic microscopy was also demonstrated to achieve virtual H&E staining of mouse brain 42 and frozen sections of bone tissue 43 . As another example, Mayerich.…”
Section: Label-free Virtual Stainingmentioning
confidence: 99%
“…c Blind inference of a trained virtual staining model. The virtual histology images are rapidly generated from label-free images using a digital computer smears 39 , as well as H&E 40 and IHC 41 staining on prostate tissue sections; photoacoustic microscopy was also demonstrated to achieve virtual H&E staining of mouse brain 42 and frozen sections of bone tissue 43 . As another example, Mayerich.…”
Section: Label-free Virtual Stainingmentioning
confidence: 99%
“…Initial studies demonstrated UV microscopy for live-cell nucleic acid and protein mass mapping with label-free biomolecular contrast 9,11,12 . Multispectral UV microscopy has also been used for label-free prostate tissue characterization 13 . Recently, UV microscopy has been demonstrated for robust hematology analysis including automated classification of various WBC subtypes and pseudo-colorization of blood smear images to mimic hematological staining 11,12,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Most men are diagnosed with low‐grade, localized prostate cancer and have a 5‐year net survival rate of 100%. However, the 5‐year survival rate drops to 32% for men diagnosed with high‐grade (grade group (GG) ≥ 3), metastatic prostate cancer [ 17 , 18 ]. Current diagnostic tests, such as the prostate‐specific antigen (PSA) blood test, lack specificity for predicting grade group (GG) ≥ 3 prostate cancer.…”
Section: Introductionmentioning
confidence: 99%